Assessment of blood parameters of pigs of different breeds and its interrelation with lifetime animal performance indicators - Svetlana Gritsenko, Alexey Belookov, Oksana Belookova, Marina Derkho, Tatiana Sereda, Oksana Vereshchaga, Daniel Koruhov, Natalya Fedoseeva (International Journal of Advanced Science and Technology, 2020)
In this article the morphological parameters and protein profile of blood of three breeds of pigs (Duroc (n=30); Yorkshire (n=91); Landrace (n=15)) are studied. The minimum number of erythrocytes in the blood of Landrace replacement gilts was 6.99±0.21 1012/l.  Yorkshire and Duroc breeds surpassed their analogues in this parameter by 4.72 and 17.59%, respectively. In pigs of Landrace breed red cells had maximum volume (MCV= 64.4±1.10 fl.) and the level of anisocytosis index 27.62±0.60%. The analysis of blood protein profile revealed that the breed had no significant influence on total protein concentration in blood. The breed influenced the urea level in the blood of pigs. The lowest concentration of the index was observed in the blood of Landrace breed animals (3.77±0.24 mmol/l; Cv=24.83%). The Duroc and Yorkshire pigs exceeded their Landrace counterparts by 9.02-9.28%.